Pengenalan Literasi Digital Siswa-Siswi SMP Rahmatullah Al Maarif Darek Lombok Tengah - Ayes Malona Siboro; Fajarani Choirunnisa; Hikmal Maulana Ramadhan; Laili Isna Febriani; Muhammad Fabian Isnaeni; M. Syahrul; Salsabila Hadi Putri Ningrum; Satriawan Pradana; Syifa Salsabila Satya Graha; Dina Eka Putri; Irwansyah Irwansyah; Nuzla Af'idatur Robbaniyyah; Salwa Salwa (Lembaga Pengembangan Kinerja Dosen, 2024)
Community service in the form of workshop on digital literacy at Rahmatullah Al-Ma'arif Darek Junior High School in Central Lombok aimed to improve students' understanding of digital literacy through a systematic evaluation process. The pre-test showed a low initial level of understanding, which significantly improved after the workshop. Statistical analysis using a t-test showed the effectiveness of the workshop in improving students' digital literacy. This research underscores the importance of ICT education and the need to include digital literacy initiatives in basic education. The findings provided additional insights for educators and policy makers in promoting digital skills among students, especially in rural areas.